Metacognitive Strategies in Academic Reading by EFL Learners - Ridha Ilma (ELITE Association Indonesia, 2023)
Metacognitive strategies are widely used by students in learning activities, often without them realizing it. They become one of crucial aspects for learners in comprehending the academic reading text. In this study, the writer describes students’ metacognitive strategies in reading comprehension. A quantitative survey was used as the design of the study. A questionnaire was the instrument used to collect the data in order to have a description of how students applied metacognitive strategies in reading and to what extent their awareness of metacognitive reading strategies was used in academic reading. There were 285 students in the English study program who filled out the questionnaire for the Survey of Reading Strategies Awareness (SORS). Metacognitive awareness of reading strategies used by college students in reading academic texts in English was problem solving (PROB), support (SUP) and global (GLOB). For EFL students, problem solving was the most used strategy. Students and other readers should adapt these reading methods and be guided by lecturers in using different methods. Key words: academic reading, metacognitive strategies.